Improvement Of Working Stations In Logistic Companies By Using Baseline Risk Identification Of Ergonomic Factors (Brief) - Santoso, Citra Sari Esa Dewi; Fhadillah, Ilham; Ramdoni, Ace; Putra, Peri Anggara; Juraida, Anita (International Journal of Psychosocial Rehabilitation, 2020)
One of the Logistics company in Bandung is a company engaged in the field of freight forwarding services. Of the various activities carried out by the company, all cutting activities at the retail division are carried out manually. This can pose a risk of MSDs. The method used in this study is the Nordic Body Maps (NBM) which is a questionnaire to identify the risk of injury, and then to follow up on the results of the NBM, the Baseline Risk Identification of Ergonomic Factors (BRIEF) method is used. In the NBM method, it is identified that the workstation that is critically experiencing complaints of muscle fatigue is retail with a score of 69. While the highest score of the MSDs risk of workers on the BRIEF method is the right shoulder at 100%. From these two results, it is then proposed a workstation design in the form of a cutting table that is able to reduce the risk of MSDs. After making improvements following the BRIEF method, the results in the calculation of the MSDs injury risk in the right shoulder decreased from 100% to 25%.